2009
DOI: 10.1192/bjp.bp.108.056143
|View full text |Cite
|
Sign up to set email alerts
|

Rural–urban migration and depression in ageing family members left behind

Abstract: BackgroundIt has been suggested that rural–urban migration will have adverse consequences for older parents left behind.AimsTo describe correlates of outmigration and to estimate any association between outmigration of children and depression in rural-dwelling older parents.MethodPopulation-based survey of 1147 parents aged 60 and over in rural Thailand. We randomly oversampled parents living without children. We defined an outmigrant child as living outside their parent’s district, and measured depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
72
2
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 24 publications
(36 reference statements)
4
72
2
6
Order By: Relevance
“…The mental health of the elderly parents was found to deteriorate after the migration of children in China and South Africa (Marchetti-Mercer 2012;Scheffel and Zhang 2015;Xie et al 2014). The evidence for Thailand is more mixed, with Adhikari et al (2011) reporting a negative association and Abas et al (2009) finding the opposite. Providing causal estimates is a common challenge (Démurger 2015), and the few studies explicitly addressing causality (Böhme et al 2015;Gibson et al 2011;Waidler et al 2016) find that emigration has no effect on the mental health (captured by various indicators, including an index of feeling happy, peaceful, tense, blue and downhearted, and feeling depressed) of the elderly staying behind in Moldova and Tonga.…”
Section: Introductionmentioning
confidence: 99%
“…The mental health of the elderly parents was found to deteriorate after the migration of children in China and South Africa (Marchetti-Mercer 2012;Scheffel and Zhang 2015;Xie et al 2014). The evidence for Thailand is more mixed, with Adhikari et al (2011) reporting a negative association and Abas et al (2009) finding the opposite. Providing causal estimates is a common challenge (Démurger 2015), and the few studies explicitly addressing causality (Böhme et al 2015;Gibson et al 2011;Waidler et al 2016) find that emigration has no effect on the mental health (captured by various indicators, including an index of feeling happy, peaceful, tense, blue and downhearted, and feeling depressed) of the elderly staying behind in Moldova and Tonga.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of adult self-rated health (SRH), observed physical function, mortality, and health-seeking behavior have found a positive associations with migration (Kuhn, 2005;Kuhn et al, 2011;Adhikari et al, 2011). Some studies of adult mental health have observed negative association with migration (Adhikari et al, 2011;Arenas and Yahirun, 2011), though other studies have found a positive association (Abas et al, 2009), suggesting that the economic returns to children's migration may not fully offset the loss of personal social support. Some studies of adult mental health have observed negative association with migration (Adhikari et al, 2011;Arenas and Yahirun, 2011), though other studies have found a positive association (Abas et al, 2009), suggesting that the economic returns to children's migration may not fully offset the loss of personal social support.…”
Section: Impacts Of Migrationmentioning
confidence: 99%
“…Terapeuti navode postojanje osjećaja ljutnje jer pacijentov recidiv smatraju osobnim neuspjehom. Zdravstveni djelatnik mora prepoznati i kontrolirati svoju ljutnju spram alkoholičara kod kojeg je verificiran recidiv, stoga se terapeuti moraju kontinuirano educirati [1,2,3,4,7,9].…”
Section: Sredinom Dvadesetog Stoljeća Kanađanin Elvin Mortonunclassified
“…; (iv) tolerancija. Potreba za pijenjem sve većih količina alkohola da bi se postiglo određeno stanje u organizmu, koje se prije postizalo pijenjem manjih količina alkohola; (v) zanemarivanje članova obitelji, radnih i drugih obveza i interesa; (vi) nastavak pijenja unatoč spoznaji o njegovoj štetnosti [1,2,3,4,5,6].…”
unclassified
See 1 more Smart Citation